2020
DOI: 10.1016/j.marpolbul.2020.111450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marine noise pollution on Mediterranean fishes and invertebrates: A review

Abstract: Highlights (3 to 5 bullet points, maximum 85 characters, including spaces, per bullet point, to be submitted in a separate editable file in the online submission system, using 'Highlights' in the file name). • Marine noise is a widespread source of pollution in the Mediterranean Sea • Noise pollution produces a multitude of impacts on marine fish and invertebrates • Marine noise pollution impacts individuals to ecosystems • A variety of measures could be adopted to mitigate marine noise pollution Abstract (max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 126 publications
0
29
0
Order By: Relevance
“…This is without considering two of the most severely undervalued services provided by the Ocean, as heat and carbon sinks, that have buffered many of the negative impacts of climate change. Many anthropogenic activities are leaving significant, direct and measurable global footprints in the Ocean with high profile examples including fishing 1,2,3, , shipping lanes (Liu et al, 2019;Pirotta et al, 2019), dredging 4 , plastic pollution (Hardesty et al, 2017;Barrett et al, 2020), noise pollution (Di Franco et al, 2020;Chahouri et al, 2021;Duarte et al, 2021), and changes in Ocean chemistry 5 .…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…This is without considering two of the most severely undervalued services provided by the Ocean, as heat and carbon sinks, that have buffered many of the negative impacts of climate change. Many anthropogenic activities are leaving significant, direct and measurable global footprints in the Ocean with high profile examples including fishing 1,2,3, , shipping lanes (Liu et al, 2019;Pirotta et al, 2019), dredging 4 , plastic pollution (Hardesty et al, 2017;Barrett et al, 2020), noise pollution (Di Franco et al, 2020;Chahouri et al, 2021;Duarte et al, 2021), and changes in Ocean chemistry 5 .…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…Studies of acoustic effects on aquatic organisms, especially fish, show that anthropogenic noise negatively influences both teleost and elasmobranch fish [7,12,13] and directly affects vocal teleost fish, increasing stress, altering their metabolic processes, and negatively affecting all stages of their life activity [5,14,15]. Most fish communicate and hear best precisely in the range of technogenic noise, below 500 Hz, by sensing particle accelerations with their inner ear [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that anthropogenic noise from ships (broadband frequency with various intensities) affects the existence of marine life. The impact on marine mammals and fishes is in the form of stress (80-170 dB) (Rolland et al, 2012;Wright et al, 2011;Kight and Swaddle, 2011), leading to behavioral (up to 176 dB) (Halliday et al, 2017), physiological (up to 130 dB) (Codarin et al, 2009;Erbe et al, 2016) and other physiological effects (up to 170 dB) (Casper et al, 2013;Di Franco et al, 2020;Tougaard et al, 2015), population dynamics (high noise level) (Nabe-Nielsen et al, 2014), as well as damage to the hearing system (172-177 dB) (Slabbekoorn et al, 2010;Halliday et al, 2017). The sources and quantities of noise produced in Cilacap waters should be investigated due to the enormous impact on aquatic biota.…”
Section: Introductionmentioning
confidence: 99%